2013
DOI: 10.4187/respcare.02419
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Albuterol Delivery in a Model of Spontaneously Breathing Children With Tracheostomy

Abstract: BACKGROUND: Nebulized therapy is commonly used in spontaneously breathing tracheostomized patients, despite a lack of recommended devices and techniques. I compared albuterol dose delivered to a model of spontaneously breathing children with tracheostomy, using different nebulizers, tracheostomy tube sizes, inhalation techniques, and breathing patterns. METHODS: A tracheostomy model was connected in series to a breathing simulator, with a filter interposed. I simulated the breathing patterns of a 16-month-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…10 Previous studies done in pediatric models of spontaneously breathing children reported that a pressurized metered-dose inhaler (pMDI) with a spacer/valved holding chamber (VHC) and a continuous output jet nebulizer used with the assisted technique delivered the highest amount of albuterol. 6,7 The same studies reported that use of the assisted technique was beneficial when used with jet nebulization but detrimental when pMDIs/VHCs were used. Other studies have shown a benefit of using the assisted technique or have been neutral.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…10 Previous studies done in pediatric models of spontaneously breathing children reported that a pressurized metered-dose inhaler (pMDI) with a spacer/valved holding chamber (VHC) and a continuous output jet nebulizer used with the assisted technique delivered the highest amount of albuterol. 6,7 The same studies reported that use of the assisted technique was beneficial when used with jet nebulization but detrimental when pMDIs/VHCs were used. Other studies have shown a benefit of using the assisted technique or have been neutral.…”
Section: Introductionmentioning
confidence: 98%
“…The amount left in the nebulizer cup was calculated by subtracting the dry weight from the weight after the 5 mL were added and then multiplying this value by the albuterol concentration. 7 This method was used as a quality control measure, and since there were no differences, results were not reported. This was done to ensure that each nebulizer cup was operating correctly and that each run received approximately the same amount of drug.…”
Section: Protocolmentioning
confidence: 99%
See 3 more Smart Citations